A population perspective to mitigating risk for second primary breast cancer. (March 2013) - Lowery, Jan T; Risendal, Betsy C
SUMMARY There are more than 2 million breast cancer survivors in the USA. Approximately 5–10% of survivors will develop a second, metachronous breast cancer within 10 years' time; a risk two- to six-times higher than that in the general population. Women who develop metachronous cancer are more likely to die from the disease compared with women with unilateral cancer. Risk factors for metachronous cancer include BRCA mutation status, young age, family history and tumor phenotype, while adjuvant chemotherapy and endocrine therapy may attenuate the risk. Surveillance guidelines recommend annual mammography, but MRI is not currently indicated for most women. An increasing number of women are choosing prophylactic contralateral mastectomy, although it is not likely to be beneficial for most women. Improved strategies are needed for identifying survivors at an increased risk in order to help guide clinical decisions regarding follow-up care. This review presents an overview of the burden and risk factors for metachronous breast cancer and discusses challenges and opportunities for a population approach to mitigating risk and adverse outcomes from these cancers.